2021
DOI: 10.3390/cancers13225793
|View full text |Cite
|
Sign up to set email alerts
|

A Multiparametric MR-Based RadioFusionOmics Model with Robust Capabilities of Differentiating Glioblastoma Multiforme from Solitary Brain Metastasis

Abstract: This study aimed to evaluate the diagnostic potential of a novel RFO model in differentiating GBM and SBM with multiparametric MR sequences collected from 244 (131 GBM and 113 SBM) patients. Three basic volume of interests (VOIs) were delineated on the conventional axial MR images (T1WI, T2WI, T2_FLAIR, and CE_T1WI), including volumetric non-enhanced tumor (nET), enhanced tumor (ET), and peritumoral edema (pTE). Using the RFO model, radiomics features extracted from different multiparametric MRI sequence(s) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The authors [ 29 ] considered these parameters a reflection of the inhomogeneity exhibited by HGGs’ PZ, an observation that is in accordance with our current and previous [ 28 ] results. Recently, a multiparametric MR-based RadioFusionOmics model [ 30 ] using combined texture parameters extracted from the tumoral and peritumoral zone was able to differentiate the two lesion categories with 85.5% accuracy, 85.6% Se, and 85.3% Sp. Interestingly, none of the above-mentioned studies extracted shape-based textural features in an attempt to differentiate between the two entities.…”
Section: Discussionmentioning
confidence: 99%
“…The authors [ 29 ] considered these parameters a reflection of the inhomogeneity exhibited by HGGs’ PZ, an observation that is in accordance with our current and previous [ 28 ] results. Recently, a multiparametric MR-based RadioFusionOmics model [ 30 ] using combined texture parameters extracted from the tumoral and peritumoral zone was able to differentiate the two lesion categories with 85.5% accuracy, 85.6% Se, and 85.3% Sp. Interestingly, none of the above-mentioned studies extracted shape-based textural features in an attempt to differentiate between the two entities.…”
Section: Discussionmentioning
confidence: 99%
“…With new machine learning algorithms (ML), radiomics analysis could be more precise, accurate, and convenient for clinical reports [1][2][3][4]6]. Predictive model can be created based on the unique patterns found in the data by using these algorithms [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies showed that combined conventional MRI (cMRI), diffusion-weighted imaging (DWI), and 18F-FDG-PET images to establish different radiomics models to differentiate MET from GBM and found that the integrated model based on cMRI, DWI, and 18F-FDG-PET had the best discriminatory power. In contrast, advanced sequences like DWI are not widely available in the clinic as cMRI [3,12,20]. Consequently, the radiomics literature shows that different classifiers have different outputs [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations